2017
DOI: 10.1128/jvi.00149-17
|View full text |Cite
|
Sign up to set email alerts
|

New Connections: Cell-to-Cell HIV-1 Transmission, Resistance to Broadly Neutralizing Antibodies, and an Envelope Sorting Motif

Abstract: HIV-1 infection from cell-to-cell may provide an efficient mode of viral spread in vivo and could therefore present a significant challenge for preventative or therapeutic strategies based on broadly neutralizing antibodies. Indeed, Li et al. (H. Li, C. Zony, P. Chen, and B. K. Chen, J. Virol. 91:e02425-16, 2017, https://doi.org/ 10.1128/JVI.02425-16) showed that the potency and magnitude of multiple HIV-1 broadly neutralizing antibody classes are decreased during cell-to-cell infection in a context-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Moreover, cell-to-cell transmission of retroviruses through the VS has been shown to play a critical role in viral dissemination in vivo ( Murooka et al, 2012 ; Sewald et al, 2015 ). In this context, studies that examined the accessibility of the VS to entry inhibitors have concluded that synapse-mediated spread is less sensitive than cell-free particle spread to neutralizing antibodies in vitro and vivo ( Abela et al, 2012 ; Gombos et al, 2015 ; Smith and Derdeyn, 2017 ; Zhong et al, 2013 ). Cell-to-cell contact sites have additionally been described as the main route of viral dissemination for the murine leukemia virus (MLV) by using live-cell imaging ( Jin et al, 2009 ).…”
Section: Modes Of Cell-to-cell Spreadmentioning
confidence: 99%
“…Moreover, cell-to-cell transmission of retroviruses through the VS has been shown to play a critical role in viral dissemination in vivo ( Murooka et al, 2012 ; Sewald et al, 2015 ). In this context, studies that examined the accessibility of the VS to entry inhibitors have concluded that synapse-mediated spread is less sensitive than cell-free particle spread to neutralizing antibodies in vitro and vivo ( Abela et al, 2012 ; Gombos et al, 2015 ; Smith and Derdeyn, 2017 ; Zhong et al, 2013 ). Cell-to-cell contact sites have additionally been described as the main route of viral dissemination for the murine leukemia virus (MLV) by using live-cell imaging ( Jin et al, 2009 ).…”
Section: Modes Of Cell-to-cell Spreadmentioning
confidence: 99%
“…It is possible that conformational changes of envelope trimers [39] induced by binding to scFvs may allow fusion inhibitors to interact with gp41 [30]. Moreover, mutations within the cytoplasmic tail of gp41 may play a crucial role in exposure of key neutralizing epitopes during cell-to-cell infection [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…To differentiate the two cell lines in mass spectrometry, SupT1 target cells were labeled for eight doublings with "heavy" amino acids, with ~100% incorporation of 13 C arginine and C 15 N lysine confirmed by mass spectroscopy, while the Jurkat producer cells were grown in normal "light" media (Fig 1A). To further focus analysis on cell contact-induced changes in producer cells and minimize downstream effects on signaling pathways [34] from cell-free infection, we transfected Jurkat producer cells with a plasmid carrying an HIV-1 provirus [38,72] expressing a GFP-NanoLuc luciferase fusion gene (Promega), and an HIV-1 Env and Nef expression plasmid [40].…”
Section: Plos Pathogensmentioning
confidence: 99%
“…In cultured cells, spread by cell-cell transfer between T cells is 100-1,000-fold more efficient than cell-free infection through the extracellular space [5][6][7][8][9]. Increasing evidence shows that direct cell-cell spread confers multiple replicative advantages to HIV-1 and may allow HIV-1 to evade aspects of the humoral immune response, innate antiviral restriction factors such as tetherin, and antiretroviral drugs [8,[10][11][12][13]. VS formation promotes infection of the target cell by focusing virion assembly and release at sites of cell-cell contact, leading to efficient HIV-1 integration and high viral gene expression in the target cell [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%